A Pilot Study of the Effects of Mindfulness-Based Cognitive Therapy on Positive Affect and Social Anxiety Symptoms - Strege, Marlene V.; Swain, Deanna; Bochicchio, Lauren; Valdespino, Andrew; Richey, John A. (Frontiers in Psychology, 2018)
Randomized controlled trials have demonstrated that mindfulness-based cognitive therapy (MBCT) is efficacious in reducing residual depressive symptoms and preventing future depressive episodes (Kuyken et al., 2016). One potential treatment effect of MBCT may be improvement of positive affect (PA), due to improved awareness of daily positive events (Geschwind et al., 2011). Considering social anxiety disorder (SAD) is characterized by diminished PA (Brown et al., 1998; Kashdan, 2007), we sought to determine whether MBCT would reduce social anxiety symptoms, and whether this reduction would be associated with improvement of PA deficits. Adults (N = 22) who met criteria for varied anxiety disorders participated in a small, open-label trial of an 8-week manualized MBCT intervention. Most participants presented with either a diagnosis (primary, secondary, or tertiary) of generalized anxiety disorder (GAD) (N = 15) and/or SAD (N = 14) prior to treatment, with eight individuals meeting diagnostic criteria for both GAD and SAD. We hypothesized participants would demonstrate improvements in social anxiety symptoms, which would be predicted by improvements in PA, not reductions in negative affect (NA). Results of several hierarchical linear regression analyses (completed in both full and disorder-specific samples) indicated that improvements in PA but not reductions in NA predicted social anxiety improvement. This effect was not observed for symptoms of worry, which were instead predicted by decreased NA for individuals diagnosed with GAD and both decreased NA and increased PA in the entire sample. Results suggest that MBCT may be efficacious in mitigating social anxiety symptoms, and this therapeutic effect may be linked to improvements in PA. However, further work is necessary considering the small, heterogeneous sample, uncontrolled study design, and exploratory nature of the study.